Taking sides : - Finsterbusch , Kurt (McGrawHill, 2011)
This book contains 42 selections presented in a pro and con format. A total of 21 different controversial social issues are debated. The sociologists, political scientists, economists, and social critics whose views are debated here make their cases vigorously.